Russia & Legal Harmonization: An Historical Inquiry into IP Reform As Global Convergence and Resistance - Boris N. Mamlyuk (Washington University Global Studies Law Review, 2011)
The Article presents information related to breaks in the intellectual property reforms of Russia and discusses the Soviet regulations on intellectual property. It further discusses the intellectual property law reform projects and attempts of harmonizing legislation through international norms. It also focuses on the normative approaches to laws and compares with the U.S. copyright laws related to fair use.
Keywords: Intellectual property; International law; Fair use (Copyright); Delegated legislation; Business